2015
DOI: 10.3389/fmicb.2015.00094
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches for prediction of pathogen-host protein-protein interactions

Abstract: Infectious diseases are still among the major and prevalent health problems, mostly because of the drug resistance of novel variants of pathogens. Molecular interactions between pathogens and their hosts are the key parts of the infection mechanisms. Novel antimicrobial therapeutics to fight drug resistance is only possible in case of a thorough understanding of pathogen-host interaction (PHI) systems. Existing databases, which contain experimentally verified PHI data, suffer from scarcity of reported interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 67 publications
0
90
0
Order By: Relevance
“…More recently, attention has been turned to the problem of predicting PPIs between pathogenic microbes and the human host towards gaining a better understanding of infectious diseases [23, 24]. Comparative methods based on local sequence alignment [3134] are bound to yield a significant proportion of false positives, or negatives, unless structural (domain-level) details about the template interactions are also properly taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, attention has been turned to the problem of predicting PPIs between pathogenic microbes and the human host towards gaining a better understanding of infectious diseases [23, 24]. Comparative methods based on local sequence alignment [3134] are bound to yield a significant proportion of false positives, or negatives, unless structural (domain-level) details about the template interactions are also properly taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Computational methods can complement and aid experimental approaches by helping to predict, or prioritize, potential interactions which could guide wet lab studies. Indeed, bioinformatic, or in silico, prediction of human-microbial PPIs has emerged as an active area of research in recent years [23, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…Even among highly connected proteins (degree k>5) in the human interactome, the degree of virus targets was twice as large as those of nontargeted proteins. Independent analyses found that viral proteins preferably target human host proteins that are involved in a large number of interactions [14,49,50,[54][55][56][57][58][59][60]. As the number of interactions is a local measure of centrality, other more global measures of centrality were considered as well.…”
Section: What Are the Protein Targets Of Human Viruses?mentioning
confidence: 99%
“…Available computational tools to predict host-pathogen interactions have been recently reviewed by Nourani et al . [93]. Current methods mostly depend on global sequence and structure homology.…”
Section: Introductionmentioning
confidence: 99%